(untitled) (Research, Society and Development, 2021)
Obstetric violence is understood as any act performed by health professionals who violate the reproductive and sexual rights of women in the gravidic-puerperal process. It was aimed by the descriptive-exploratory study of qualitative and quantitative approach, to identify the recognition of 24 users of the public network as pregnant women, puerperal women and mothers of children up to two years on the theme, associated with the work of eight psychologists in the social assistance and health contexts of the city of Birigui/SP. It resulted that 96% of women did not recognize the violence suffered, however, reported abusive practices and dehumanized attention. Six psychologists interviewed did not attend to victims of obstetric violence. It was concluded that it is indispensable the look at psychology in the investigation and confrontation of violence, promoting women’s empowerment and the preservation of woman’s subjectivity.